Syntactic and lexical complexity in written L2 English : A comparative study of Finnish and Hungarian university-level students - Hesso, Iina (My University, 2024)
This thesis aims to compare syntactic and lexical complexity in essays written by Finnish and Hungarian university-level English language students and examine how syntactic structures and lexical elements manifest in observed high-complexity and low-complexity essays. Thirty essays by Finnish students and thirty essays by Hungarian students from the ACALEX corpus were utilised as the primary data for the analysis. Syntactic complexity and lexical complexity were measured by using web-based interfaces of automatic analyser tools The L2 Syntactic Complexity Analyzer and The Lexical Complexity Analyzer. The results were further analysed in Microsoft Excel and IBM SPSS Statistics 27. Finally, a qualitative extreme case analysis was conducted based on the statistical analysis’ results. In the quantitative analysis, it was discovered that Finnish students, on average, display higher syntactic and lexical complexity in their essays than Hungarian students. Finnish students, on average, tend to produce longer syntactic structures, use more complex grammar, and write more lexically dense language with more variation and sophistication in word choices than Hungarian students. The qualitative analysis revealed that high complexity may manifest in the choice of long syntactic structures and varied sophisticated lexical elements. Low complexity is characterised by short syntactic structures, repetition of words, and a lack of sophistication in vocabulary. The results of the thesis, thus, suggest that phenomena such as written learner language, L1 background, and linguistic complexity in L2 can affect each other in various ways. Therefore, the findings indicate that these phenomena should be considered in foreign language instruction for effective language learning.
Keywords: syntactic complexity, lexical complexity, linguistic complexity, learner language, L2 proficiency